“Fortunately”: Oral history of a Salvadoran family and their North-South migration. - L. López, Maité Cristina (2020)
The objective of this essay is to accompany, through testimony, oral tradition of Latin American, our Salvadoran co-writer on her migration journey from El Salvador to Costa Rica.  To open ourselves to the experiential richness that emerges from words and memories as a mirror of our Central American and Costa Rican realities.  From the voice of our collaborator, a Central America appears with a history of colonial, imperialist and capitalist imposition that sows, on our rich lands, a culture of pervasive violence, from the wombs of women to the nation States, whose birthed fruits are necropolitics, xenophobia and sociocultural and economic poverty of our peoples.